(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Few healthcare provider (HCP) training programmes provide consistent and dedicated time in their curricula for physical activity (PA) training. Thus, continuing education efforts are needed to provide current HCPs with guidance and support in promoting PA with their patients. While there are numerous PA training programmes (PATP) offered globally, many are offered in-person and there is little standardisation of this training. This presentation will describe the development of a standardised, globally-offered PA training programme (PATP) and its virtual adaptation for offer at local levels by health departments. Methods: In 2016, leaders from around the world met to discuss standardising a PATP curricula to be offered across the Exercise is Medicine global network. These discussions led to the integration of best practices from the various trainings around six key topics into one standardised PATP. The new PATP was disseminated back to global partners for widespread use in 2018. In 2019, the PATP was adapted to an online format for use in the US, followed shortly thereafter by a similar adaptation into Spanish in Latin America. Results: The updated 2018 PATP was adopted and implemented into practice by partners around the world, particularly in Asia (Malaysia, Singapore, Taiwan), Europe (Italy, Spain) and South America (Brazil, Chile, Colombia). In Singapore, a textbook was developed to supplement the PATP training course, which was subsequently adopted by the Army and Singaporean medical schools. The original PATP was translated into Spanish and offered in a virtual format across Central and South America, reaching >1,500 HCPs between 2018–22. In 2019, a year-long process was taken to transfer the PATP into an online format for the Tennessee Department of Health and rolled out in 2022 as a part of a new statewide continuing education programme for HCPs. Conclusions: Core concepts for PATPs are consistent and can be standardised for coordinated dissemination around the world, while being tailored to fit local needs. Over time, there is a natural ‘drift’ away from the standardised PATP, requiring periodic updating and ongoing collaboration. Support/Funding Source: None. Keywords: Continuing education, medicine, nursing, physical activity, training